IMPLEMENTATION OF BLENDED LEARNING ON PHYSICS SUBJECTS TOWARDS IMPROVING STUDENT LEARNING OUTCOMES - S. Ratih Uswatun Khasanah, S.Si (Direktorat GTK Madrasah Ditjen Pendis Kementerian Agama Republik Indonesia, 2021)
The problems are encountered in learning physics class XI is the low result study, especially on optics. Interest research is to know what is learning that is done in Blended Learning can improve the outcomes of learning of students, especially in optics at XI class MAN 1 Siak. This is a research action class, sample students class XI.2 which totaled 20 people. The resultu of learning, the students were taken to the engineering test and observation, the result of test obtained by the value of the mean average 56.80 into 85.60 with SD= 11.35 and 95% of students get the cycle I to cycle II. Clonclusion of research is that learning by the blended learning cen improving the result of learning of students in the discussion of optics.